Strategi Pemberdayaan Ekonomi Pelatihan Produksi Sirup dan Permen Buah Pedada, Pemasaran Online melalui Website, dan Pengembangan Paket Wisata untuk Meningkatkan Kesejahteraan Masyarakat - Darmanto, Darmanto; Martanto, Martanto; Nova Zulfahmi, A (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Kuala Satong Village, situated in the North Matan Hilir District of Ketapang Regency, possesses a 6-hectare mangrove forest region managed by the village Pokdarwis and various environmental organisations. Despite being a tourist destination, several obstacles are faced, such as the non-utilisation of mangrove forest products to become products that have economic value, the sub-optimal management of tour packages, and the lack of community understanding regarding promotion through the website. In an effort to increase the economic value of the community, community service activities are carried out through pedada fruit processing, website management training, social media content, and CHSE standard homestays. The focus is on understanding tour packages to increase visitor attraction. The method of implementing activities includes lectures, questions and answers, demonstrations, and hands-on practice. The purpose of the service is to increase community knowledge in utilising pedada fruit economically and support the development of Mangrove Forest tourism as a leading destination. The use of the website is expected to increase tourism publications and superior products of Kuala Satong Village. The results of the training are expected to have a positive impact on increasing community income and supporting local economic growth through sustainable product marketing.